Experimental approach, theoretical investigation and molecular docking of 2- chloro-5-fluoro phenol antibacterial compound. Issue 11 (November 2020) - Vidhya, V.; Austine, A.; Arivazhagan, M.
Abstract: The molecular structural dimerization of biologically potent 2-chloro-5-fluoro phenol (2C5FP) is optimized. A combined experimental and theoretical characteristics of vibrational spectral determinations (NMR, FT-IR and Raman) on 2-chloro-5-fluoro phenol (2C5FP) were used at DFT-B3LYP/6–31++G (d, p) level of computation. A close coherence is achieved when experimentally observed wave numbers are compared with calculated wave numbers by refinement of the scale factors. Calculated values of global chemical descriptors of the present molecule reveal significant molecular stability and chemical reactivity. Non-Linear optical (NLO) property of the present molecule is investigated by determining the second order non linear parameter of first hyperpolarizability β. Moreover, hydrogen bond and thermodynamic parameters at various temperatures are determined and discussed. Investigated compound 2C5FP possesses a better antibacterial activity against Echerichia coli, Streptococcus aureus, Pseudomonas aureus, and Staphylococcus aureus, respectively. The title molecule is subjected to molecular docking studies with two different proteins, namely Staphylococcus aureus Tyrosyl-tRNA synthetase (PDB ID: 1JIL) and human dihydroorotate dehydrogenase (hDHODH) (PDB ID: 6CJF). The results of molecular docking analysis support the antibacterial activity and demonstrate a strong interaction with the DHODH inhibitor. Abstract : DFT, Dimer, NLO, Antibacterial activity, Molecular docking; Computational materials science; Materials characterization; Structural analysis; Structural behavior; Computational chemistry; Organic chemistry; Molecular modeling; Pharmaceutical chemistry; Microbiology; Pharmaceutical science.